2012
DOI: 10.1186/gm340
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulatory network inference: evaluation and application to ovarian cancer allows the prioritization of drug targets

Abstract: BackgroundAltered networks of gene regulation underlie many complex conditions, including cancer. Inferring gene regulatory networks from high-throughput microarray expression data is a fundamental but challenging task in computational systems biology and its translation to genomic medicine. Although diverse computational and statistical approaches have been brought to bear on the gene regulatory network inference problem, their relative strengths and disadvantages remain poorly understood, largely because com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 80 publications
(97 reference statements)
2
96
0
4
Order By: Relevance
“…Deciphering GRNs from rapidly growing microarray expression databases has been shown to be a very promising approach e.g. in cancer research [16,17]. Many tools are emerging and have been used for constructing, inferring and analyzing such GRNs.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…Deciphering GRNs from rapidly growing microarray expression databases has been shown to be a very promising approach e.g. in cancer research [16,17]. Many tools are emerging and have been used for constructing, inferring and analyzing such GRNs.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…Phenotype to genotype research has produced informatics resources such as the Phenoscape Knowledgebase (Phenoscape KB; http://kb.phenoscape.org) [14] and the Phenotype-Genotype Integrator (PhenGenI; www.ncbi.nlm.nih.gov/gap/phegeni) [20]; researchers using these resources have been able to verify key phenotype-genotype relationships [19]. Many tools also exist for the reverse engineering of GRNs from microarray datasets [15][25] [16]. Networks obtained from reverse engineered microarrays or next generation sequencing (NGS) datasets constitute a big knowledge opportunity for studying the connections between intracellular systems, metabolic interaction models, and transcriptomics [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that including other kinds of information leads to biologically more accurate results [5]. Of great interest is the Machine Learning category, under which are included algorithms based on Random Forest (GENIE3 [6]), Support Vector Machines (SVM) (SIRENE [7]) and Neural Networks (ENFRN [8]), because by construction these methods can embed a priori knowledge.…”
Section: Introductionmentioning
confidence: 99%